Gender differences: Participation in agricultural production in Ethiopia - Gudina Yadeta; Gudina Abashula Fojo (Harmoni Sosial: Jurnal Pendidikan IPS, 2019)
Women occupy disadvantaged position despite their immense labor contributions to paid and unpaid activities. This study investigated gender differences pertaining to domestic and agricultural activities. The study employed a cross sectional survey design with a mixed research approach of data collection and analysis. Among 17th kebeles that are found in Yayo district, Witate and Hamuma were selected purposively. By doing so, among the total 2060 husbands and wives who live together, 324 of them were picked randomly by using Raosoft sample size determination formula. Descriptive statistics, independent T-test and chi-square were used as quantitative methods of data analysis were as thematic analysis was used as a qualitative method of data analysis. The study revealed that rural women had higher participation in agricultural activities such as weeding, threshing and storing, marketing and livestock management than men. Chi-square test showed that there were an association between gender and participation in decision making with regard to using agricultural inputs, poultry production and household expenditures. With regard to participation in human capitals such as training on agriculture and rural development, chi-square showed significant gender differences between responding husbands and wives. Therefore, it demands an effective policy intervention and awareness creation to address women’s working conditions.